Does mixed spices affect serum insulin and adiponectin concentration in male sprague dawley rats? - Khattak, Muhammad Muzaffar Ali Khan; Abu Bakar, Ibrahim; Mamat, Nik Mazlan; Mohd Abu Bakar, Wan Azdie; Mohd Shukri, Nor Azwani (Science and Education Publishing, 2014)
Spices are used in food around the world with a view to enhance the flavour/aroma of dietary preparations. Apart from this aspect spices are also used in herbal medicines practice/treatment. However, the effect of mixed spices namely cinnamon (Cinnamomum zeylanicum), cloves (Syzygium aromaticum or Eugenia caryophyllata), turmeric (Curcuma longa), and bay leaves also known as curry leaf (Murraya koenigii) on serum glucose, insulin and adiponectin protein concentration in rats induced hyperglycemia with streptozotocin (STZ) have not been studied. Sprague Dawley rats aged three months were injected with STZ (40mg/kg body weight) in the abdomen in order to induce hyperglycemia. The rats were acclimatized with diets prior allocation to the doses of mixed spices. After having developed hyperglycemia, the rats were divided into four groups i.e. 0 (control), one, two and three g per day. The aforementioned spices were ground and mixed in equal ratios and added to stock diets 0, 1, 2 and 3 gram of the mixed spices in the feed to be fed to rats daily. The total duration of the feeding was 40 days and followed by 20 days after effect of the spices. Blood was collected on the day 0, 21, 31, 41 from the tail and on the 61st day from heart puncture of the rats. The blood samples were immediately processed for serum separation after day 61 collection and stored for later analysis at -70 C. The serum was analyzed for adiponectin protein, insulin and glucose. The statistical analysis of the results indicated that serum adiponectin protein and insulin concentration were significantly (P<0.05) higher whereas serum triglycerides concentration was significantly (P<0.05) lower in three gram fed spices compared to control 1 and 2 gram spices fed groups. This study indicates that spices provide control over hyperglycemia through increased adiponectin and insulin in circulating blood. Therefore, these spices combination may be used for the control of hyperglycaemia in type 2 diabetic patients.